Type of input and syllabic processing of words in Parkinson’s disease - Rodríguez Riaño, Leidy Johanna; Baquero Castellanos, Silvia; Álvarez, Carlos J.; Müller, Oliver (Revista de Investigación en Logopedia, 2023)
Persons with Parkinson's disease (PD) show writing difficulties, which might indicate alterations of the linguistic-cognitive planning or the mechanics of writing. This study aims at establishing whether persons with mild PD experience alterations of phonological-syllabic processing in writing and whether input modality (auditory or pictorial) influence access to syllabic units. Twenty participants with PD and 20 controls wrote down Spanish words. An auditory word or a picture was presented to indicate the word to be written. We compared words with the same two letters belonging to different syllables (a and r in ba.res, intersyllabic) or to the same syllable (bar.ba, intrasyllabic). The duration of the pause between those two letters was measured (interval 2: I2). The elderly persons of the control group evidenced a longer I2 in the intrasyllabic condition, independently of input modality, which implies a functional role of the syllable in the planning of writing, as found before in young adults. The persons of the PD group only showed this effect with auditory input, not with pictorial input. This suggests that the syllable acts as a phonological processing unit for writing with auditory input, which also activitates phonological processes. On the contrary, the visual processing of the pictures seems to interfere with the typical writing process.
Keywords: Parkinson's disease; language; writing; syllable; neuroscience